PRAGMATISME KOMUNIKASI MASYARAKAT PEDESAAN (REKONSTRUKSI RUANG SOSIAL PENGGUNAAN TELEPON SELULER DI PEDESAAN) - Abdul Halik (Fakultas Dakwah dan Komunikasi, 2017)
The use of mobile phone in interpersonal communication is not only used by urban society, but also by rural society. The structure of social, culture, and norms which are clasically owned by the rural society has been displaced. The rural society construct their values and social communication act as the concequence of the use of mobile phone massively. The change of the rural society production activity has direclty boosted the social space. The pattern of social interaction is used to be collective, but now to be individual. The elements which are developed social interaction in rural area are moving dinamically and able to reproduce social values such as individualistic, effectivity, and pragmatism.